Acidentes de trabalho no Brasil de 2007 a 2015: indicadores e previsão de acidentes - Sieminkoski, Tiago (2017)
Occupational accidents have been investigated by governments and researchers to identify causal links, with the aim of proposing actions to minimize them. The objective of this study is to analyze the occupational accidents of the INSS Yearbooks between 2007 and 2015, surpassing the profile of the victims of industrial accidents in Brazil together with the prediction of occupational accidents for the year 2016. Through a systematic analysis it was formed a portfolio of articles published in 3 bibliographic databases in the last 10 years, this analysis showed that most of the studies aim to reduce the occurrence of occupational accidents and also presented some gaps such as the analysis of accident trends of job. Using the public data of the Statistical Yearbook of Occupational Accidents from 2007 to 2015, four time series were created for work accidents: with CAT; Typical; Path and Diseases, and through the application of techniques for analysis of time series of the STATGRAPHICS program, it was tried to identify the model that can best predict the future behavior of occupational accidents, in which ARIMA models, according to the AIC criteria, were more effective for forecasting. For the series with CAT and Typical generated the forecast shows a decrease in the occurrences of occupational accidents and for the series Path and Disease, the result infers stationarity. Despite of the decrease in registrations, for the year 2016 the prediction is that occur more than 477 thousand accidents at work. In order to find out the profile of the victims, the data of the Statistical Yearbook of Social Security between the periods 2007 to 2015 were analyzed. Male workers between 20 and 29 years in the occupation of service workers suffer more typical accidents. Findings show that this profile persisted throughout the investigated years, except for the age group, some perceived oscillations may cause changes in this profile for the next years, both for gender as well for as more incidental occupations, indicating that preventive measures should be focused on the female workers, mainly in road accidents and for occupations as middle level technicians in the biological, biochemical, health and related sciences.